2010
DOI: 10.1242/dev.045310
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αV is necessary for gastrulation movements that regulate vertebrate body asymmetry

Abstract: Integrin αV can form heterodimers with several β subunits to mediate cell-cell and cell-extracellular matrix interactions. During zebrafish gastrulation, αV is expressed maternally and zygotically. Here, we used a morpholino-mediated αV knockdown strategy to study αV function. Although αV morphants displayed vascular defects, they also exhibited left-right body asymmetry defects affecting multiple visceral organs. This was preceded by mislocalization of dorsal forerunner cells (DFCs) and malformation of the Ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 60 publications
(84 reference statements)
5
53
2
Order By: Relevance
“…However, in these phenotypes, some DFCs remained capable of interacting with others to form small groups of cells, implying that other factor(s) may contribute to DFC clustering. It has been reported that integrin αV and integrin β1b have a role in DFC clustering (26) and that planar cell polarity signaling regulates cell adhesion between DFCs (27). Additional experiments to clarify the relationship between FGF signaling and integrins or planar cell polarity signaling during DFC cluster formation will be important to understand the entire mechanism underlying DFC cluster formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these phenotypes, some DFCs remained capable of interacting with others to form small groups of cells, implying that other factor(s) may contribute to DFC clustering. It has been reported that integrin αV and integrin β1b have a role in DFC clustering (26) and that planar cell polarity signaling regulates cell adhesion between DFCs (27). Additional experiments to clarify the relationship between FGF signaling and integrins or planar cell polarity signaling during DFC cluster formation will be important to understand the entire mechanism underlying DFC cluster formation.…”
Section: Discussionmentioning
confidence: 99%
“…Perturb Laterality Organ Development-In a recent study we showed that antisense MO-mediated depletion of the integrin ␣V and ␤1b subunits leads to defective DFC migration during zebrafish gastrulation (12). DFCs are the precursor cells of the KV, a ciliated organ involved in zebrafish left-right body axis specification (20,21) Disorganized DFC migration in ␤1b morphants impedes KV formation, resulting in left-right defects in zebrafish (12).…”
Section: Mrnas That Encode Mutant Integrin ␤1b Cytoplasmic Tailsmentioning
confidence: 99%
“…DFCs are the precursor cells of the KV, a ciliated organ involved in zebrafish left-right body axis specification (20,21) Disorganized DFC migration in ␤1b morphants impedes KV formation, resulting in left-right defects in zebrafish (12). Because integrin ␤ cytoplasmic tails represent a major signaling hub for integrin interaction with cellular proteins involved in integrin signaling (22), we first explored the signaling potential of the integrin ␤1b tail in the DFC-to-KV organization processes by taking advantage of the dominantnegative effects of integrin ␤1b overexpression (22)(23)(24).…”
Section: Mrnas That Encode Mutant Integrin ␤1b Cytoplasmic Tailsmentioning
confidence: 99%
“…Fibronectin participates in the development of embryonic L-R asymmetry, by controlling the organization of cells into a single layer in the mouse node, without affecting cilia length (Pulina et al, 2011). In zebrafish, integrin α5 is expressed in the dorsal forerunner cells and is required for the morphogenesis of a single intact KV (Ablooglu et al, 2010).…”
Section: Research Article Laminin and Organ Lateralitymentioning
confidence: 99%
“…For example, disruption of integrinα5β1 or fibronectin during gastrulation affects the development of the node/KV in zebrafish and Xenopus, resulting in defective L-R asymmetry (Ablooglu et al, 2010;Pulina et al, 2011). Studies in mouse and Xenopus have shown that proteoglycans facilitate and provide directional cues for rapid propagation of Nodal and Lefty signaling from the node to the left LPM (Oki et al, 2007), and subsequently from the left to the right LPM (Oki et al, 2007;Marjoram and Wright, 2011).…”
Section: Introductionmentioning
confidence: 99%